Government Strategies Using AI: A Case Study of Cultural Heritage Restoration (Soldier Photo Collection) for South Korea’s 70th Ceasefire Commemoration - Maharani, Monica; Salim, Tamara Adriana (Universitas Airlangga, 2024)
Latar belakang: Pelestarian dan restorasi warisan budaya sangat penting untuk menjaga narasi sejarah dan identitas budaya. Tujuan: Penelitian ini mengeksplorasi peran kecerdasan buatan (AI) dalam restorasi foto sejarah Korea Selatan, khususnya dari era Perang Korea, dengan fokus pada teknologi seperti Face Image Restoration (GFP-GAN) untuk mengonversi foto hitam-putih menjadi gambar berwarna beresolusi tinggi. Proyek ini, yang dilaksanakan oleh Universitas Sungkyunkwan dan Kementerian Patriot dan Veteran Korea Selatan, menyoroti dampak signifikan AI dalam pelestarian budaya. Peran pemerintah sangat vital dalam proyek ini, dari memilih foto bersejarah hingga memastikan akurasi historis dan penerapan teknologi yang canggih. Kerja sama antara pemerintah dan institusi akademis menunjukkan bagaimana dukungan pemerintah dapat mempercepat dan memperluas teknologi pelestarian budaya. Metode: Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus dan tinjauan pustaka yang komprehensif dalam mengumpulkan data. Hasil: Hasil penelitian menunjukkan bahwa AI tidak hanya meningkatkan kualitas visual dan aksesibilitas gambar sejarah tetapi juga menghubungkan masa lalu dan masa kini secara lebih relevan. Studi ini menggarisbawahi potensi transformasional AI dalam pelestarian budaya dan menyerukan eksplorasi lebih lanjut tentang penerapannya dalam upaya global. Kesimpulan: Penelitian ini juga menekankan pentingnya kolaborasi lintas sektor antara pemerintah, akademisi, dan lembaga swasta untuk mencapai hasil restorasi yang signifikan dan bertahan lama. Background: Preserving and restoring cultural heritage is crucial for maintaining historical narratives and cultural identity. Purpose: This study investigates the role of artificial intelligence (AI) in the restoration of historical photographs from South Korea, particularly those from the Korean War era. It focuses on technologies such as Face Image Restoration (GFP-GAN) to convert black-and-white photos into high-resolution, colorized images. The project, conducted in collaboration with Sungkyunkwan University and the South Korean Ministry of Patriots and Veterans Affairs, highlights the significant impact of AI on cultural preservation. The government's role is essential in this project, encompassing tasks from selecting historical photographs to ensuring historical accuracy and the application of advanced technology. The partnership between government bodies and academic institutions illustrates how government support can accelerate and expand the application of preservation technologies. Methods: This research employed a qualitative methodology, using a case study approach alongside a comprehensive literature review to gather essential data. Results: The findings demonstrate that AI not only enhances the visual quality and accessibility of historical images but also creates a more meaningful connection between past and present. This study underscores the transformative potential of AI in cultural preservation and calls for further exploration of its application in global preservation efforts. Conclusion: It also emphasizes the importance of cross-sector collaboration among government, academia, and private organizations to achieve significant and enduring results in heritage restoration.